2018
DOI: 10.4254/wjh.v10.i9.612
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome does not affect sustained virologic response of direct-acting antivirals while hepatitis C clearance improves hemoglobin A1c

Abstract: AIMTo determine whether successful treatment with directacting antivirals (DAA) is associated with improvements in hemoglobin A1c (HbA1c) and if type 2 diabetes mellitus (T2DM) or metabolic syndrome affects sustained virologic response (SVR).METHODSWe performed a retrospective analysis of all hepatitis C virus (HCV) patients at the VA Greater Los Angeles Healthcare System treated with varying DAA therapy between 2014-2016. Separate multivariable logistic regression was performed to determine predictors of HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…The effect of MetS on the response of DAA to treatment was limited. One recent study reported that MetS did not negatively affect the sustained viral response (SVR) …”
Section: Chronic Hepatitis Viral Infection and Metabolic Syndromementioning
confidence: 99%
“…The effect of MetS on the response of DAA to treatment was limited. One recent study reported that MetS did not negatively affect the sustained viral response (SVR) …”
Section: Chronic Hepatitis Viral Infection and Metabolic Syndromementioning
confidence: 99%
“…Insulin resistance did not impair the response of CHC patients treated with DAAs 29 . Currently, many studies on DAA treatments for HCV have also demonstrated the potential benefit in glucose metabolism after SVR [30][31][32][33][34][35][36] . A retrospective single-center observational study from Philip Weidner et al investigated 281 patients receiving DAA ± Ribavirin and measured FPG.…”
Section: Continuedmentioning
confidence: 99%
“…The HbA1c level fell shortly after LDV/SOF. The results in this study revealed a decline of HbA1c in both DM and non‐DM patients following the SVR, indicating that better sugar control may be a favorable result of successful DAA treatment in CHC patients . However, parameters associated with insulin, insulin resistance, and beta‐cell function remained unchanged in this study.…”
Section: Discussionmentioning
confidence: 53%
“…The results in this study revealed a decline of HbA1c in both DM and non-DM patients following the SVR, indicating that better sugar control may be a favorable result of successful DAA treatment in CHC patients. [30][31][32] However, parameters associated with insulin, insulin resistance, and beta-cell function remained unchanged in this study. The long-term effect of the successful clearance of HCV by DAA on insulin activity and insulin resistance is of interest and important to investigate.…”
Section: Discussionmentioning
confidence: 54%